Staging That Summer in Paris: Narrative Strategies and Theatrical Techniques in the Life Writing of Morley Callaghan - Perz, Marianne (Studies in Canadian Literature, 1997)
Drawing from Evelyn Hinz’s new poetics of life writing, Perz suggests a parallel between auto/biography and drama. Just as a stage director employs stagecraft for the production of a drama, a life writer uses it to shape the way that he or she recreates life experience. Canadian writer Morley Callaghan dabbled in techniques of the stage when writing his memoir That Summer in Paris. In this text, Callaghan creates a narrative persona for his voice that performs the same tasks as a casting director, a lighting designer, and a costume designer.